2006
DOI: 10.3892/ijo.29.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of DNA binding protein A transgenic mice

Abstract: Abstract.We recently reported that the expression of dbpA (DNA binding protein A) is associated with advanced stages of human hepatocellular carcinoma (HCC) and that its transcription is positively regulated by E2F1, which is also implicated in hepatocarcinogenesis. To study the in vivo effect of dbpA on hepatocarcinogenesis, we generated the dbpA-transgenic mouse that specifically expressed a transgene in hepatocytes. Here, we studied the effect of dbpA on the expression of other cellular genes by using micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The current study demonstrated that the proportions of probes up‐regulated or down‐regulated significantly (fold changes ≥ 2) between group KD‐1, 2, 3 and group NC‐1, 2, 3 covered 3.66% (181/49395) and 8.04% (397/49395) of the total number of probes, respectively, indicating that a variety of genes altered their expression levels in CRC cells with dbpA knockdown. Consistent with the finding of Tobita et al (), who demonstrated that dbpA knockdown significantly changed the expression profiles of carcinogenesis‐related genes in human hepatocellular carcinoma (HCC), in our study, the most significantly altered genes were also associated with the development of oncogensis. For example, CFL2 (Cofilin 2) is a small ubiquitous protein and is an essential regulator of cancer cell motility and invasion (Yamaguchi and Condeelis, ); EREG (recombinant human Epiregulin) belongs to the epidermal growth factor (EGF) family and is related to differentiation, migration, and adhesion of tumor cells in gastric cancer (Yun et al, ) and colorectal cancer (Saridaki et al, ); SESN2 (sestrin 2), a p53‐regulated member of the sestrins family, has demonstrated that decreased expression of SESN2 was associated with poor prognosis in CRC patients (Wei et al, ); CXCL3 (chemokine [C‐X‐C motif] ligand 3) and CXCL1 (chemokine [C‐X‐C motif] ligand 1) as the chemokine CXC motif ligands facilitated cell migration and invasion in various types of cancers including CRC (McLean et al, ; See et al, ; le Rolle et al, ); On the other hand, among the 397 significantly down‐regulated probes (fold changes ≥ 2), PRDM10 (PR domain containing 10) as a tumor suppressor inhibited tumor metastases in undifferentiated pleomorphic sarcoma (UPS) (Hofvander et al, ); PCDH19 (protocadherin 19) also worked as a tumor suppressor and is associated with poor prognosis for patients with gastric cancer (Yu et al, ) and glioma (Wang et al, ); SRSF8 (serine/arginine‐rich splicing factor 8) is a member of the SR protein family and plays a positive role in inducing cell cycle arrest and apoptosis in colon cancer cells (Kurokawa et al, ); FGFBP1 (fibroblast growth factor‐binding protein 1) is required for embryonic vascular permeability (Tassi et al, ), and enhances the angiogenic activity in human cancers (Ray et al, ); TFF2 (trefoil factor 2) as a small peptide secreted from the gastric mucosa has been reported to be overexpression in human CRC (Yu et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study demonstrated that the proportions of probes up‐regulated or down‐regulated significantly (fold changes ≥ 2) between group KD‐1, 2, 3 and group NC‐1, 2, 3 covered 3.66% (181/49395) and 8.04% (397/49395) of the total number of probes, respectively, indicating that a variety of genes altered their expression levels in CRC cells with dbpA knockdown. Consistent with the finding of Tobita et al (), who demonstrated that dbpA knockdown significantly changed the expression profiles of carcinogenesis‐related genes in human hepatocellular carcinoma (HCC), in our study, the most significantly altered genes were also associated with the development of oncogensis. For example, CFL2 (Cofilin 2) is a small ubiquitous protein and is an essential regulator of cancer cell motility and invasion (Yamaguchi and Condeelis, ); EREG (recombinant human Epiregulin) belongs to the epidermal growth factor (EGF) family and is related to differentiation, migration, and adhesion of tumor cells in gastric cancer (Yun et al, ) and colorectal cancer (Saridaki et al, ); SESN2 (sestrin 2), a p53‐regulated member of the sestrins family, has demonstrated that decreased expression of SESN2 was associated with poor prognosis in CRC patients (Wei et al, ); CXCL3 (chemokine [C‐X‐C motif] ligand 3) and CXCL1 (chemokine [C‐X‐C motif] ligand 1) as the chemokine CXC motif ligands facilitated cell migration and invasion in various types of cancers including CRC (McLean et al, ; See et al, ; le Rolle et al, ); On the other hand, among the 397 significantly down‐regulated probes (fold changes ≥ 2), PRDM10 (PR domain containing 10) as a tumor suppressor inhibited tumor metastases in undifferentiated pleomorphic sarcoma (UPS) (Hofvander et al, ); PCDH19 (protocadherin 19) also worked as a tumor suppressor and is associated with poor prognosis for patients with gastric cancer (Yu et al, ) and glioma (Wang et al, ); SRSF8 (serine/arginine‐rich splicing factor 8) is a member of the SR protein family and plays a positive role in inducing cell cycle arrest and apoptosis in colon cancer cells (Kurokawa et al, ); FGFBP1 (fibroblast growth factor‐binding protein 1) is required for embryonic vascular permeability (Tassi et al, ), and enhances the angiogenic activity in human cancers (Ray et al, ); TFF2 (trefoil factor 2) as a small peptide secreted from the gastric mucosa has been reported to be overexpression in human CRC (Yu et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…2) between group KD-1, 2, 3 and group NC-1, 2, 3 covered 3.66% (181/49395) and 8.04% (397/49395) of the total number of probes, respectively, indicating that a variety of genes altered their expression levels in CRC cells with dbpA knockdown. Consistent with the finding of Tobita et al (2006), who demonstrated that dbpA knockdown significantly changed the expression profiles of carcinogenesis-related genes in human hepatocellular carcinoma (HCC), in our study, the most significantly altered genes were also associated with the development of oncogensis. For example, CFL2 (Cofilin 2) is a small ubiquitous protein and is an essential regulator of cancer cell motility and invasion (Yamaguchi and Condeelis, 2007); EREG (recombinant human Epiregulin) belongs to the epidermal growth factor (EGF) family and is related to differentiation, migration, and adhesion of tumor cells in gastric cancer (Yun et al, 2012) and colorectal cancer (Saridaki et al, 2011); SESN2 (sestrin 2), a p53-regulated member of the sestrins family, has demonstrated that decreased expression of SESN2 was associated with poor prognosis in CRC patients (Wei et al, 2015); CXCL3 (chemokine [C-X-C motif] ligand 3) and CXCL1 (chemokine [C-X-C motif] ligand 1) as the chemokine CXC motif ligands facilitated cell migration and invasion in various types of cancers including CRC (McLean et al, 2011;See et al, 2014;le Rolle et al, 2015); On the other hand, among the 397 significantly down-regulated probes (fold changes !…”
Section: Discussionsupporting
confidence: 92%
“…Silencing of dbpA with siRNA upregulated the expression of E-cadherin, downregulated the expression of APC, β-catenin and cyclin D1, and had no effect on NF-kB. Previous studies indicated that dbpA can regulate cell proliferation in epithelial cells [9] . Our results suggest that dbpA might be involved in abnormal proliferation, not only in gastric cells, but also in gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 95%
“…DbpA has been shown to promote cell proliferation by regulating the expression of cyclin D1 and proliferating cell nuclear antigen in vitro [8] . Expression of dbpA mRNA is enhanced in transgenic mice by upregulated carcinogenesis-related genes, such as insulin-like growth factor binding protein 1 [9] . In addition, studies have indicated that dbpA is positively regulated by E2F1 and is involved in hepatocarcinogenesis in vitro [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also demonstrated that both NPM and TFF3 are involved in the regulation of apoptosis via the NF-κB pathway (7,8,19). Tobita et al (29) reported that E2F1, which is implicated in hepatocarcinogenesis, may increase the expression of TFF3 by upregulating DNA-binding protein A, which is associated with advanced stages of human hepatocellular carcinoma. In addition, the activation of E2F1 is regulated by NPM̸B23 via modulating the promoter binding of NF-κB (8).…”
Section: Medianmentioning
confidence: 99%